Sequential herbicide application coupled with mulch enhances the productivity and quality of winter onion (Allium cepa L.) while effectively controlling the mixed weed flora - Kaur, Ramanjit; Bana, R. S.; Singh, Teekam; Meena, S. L.; Raj, Rishi; Dass, Anchal; Govindasamy, Prabhu; Gill, Jasvir Singh; Kumar, Sunil; Sen, Suman; Kumar, Shital; Choudhary, Anil K.; et al. (Frontiers in Sustainable Food Systems, 2024)
Weed control poses substantial difficulties for winter season onion (Allium cepa L.) cultivation in the north-western Indo-Gangetic Plains, primarily due to the constrained efficacy of the existing herbicides. To address this issue, a 2-year field study was conducted to assess the efficacy of pre- and post-emergence herbicides (pendimethalin, ethoxysulfuron, imazethapyr, and quizalofop-p-ethyl) individually and in combination with crop residue mulch for weed control in winter onion. The results revealed that using herbicides or mulches in isolation did not provide satisfactory weed control. However, the integration of natural mulch with pendimethalin followed by quizalofop-p-ethyl application proved to be the most effective weed control strategy, resulting in the least reduction in bulb yield (10.3%) compared to other treatments. On the contrary, combinations of pendimethalin with ethoxysulfuron or imazethapyr showed adverse effects on the onion crop and inflicted the highest yield losses among all treatments (78.6 and 83.4%, respectively). However, the combination of pendimethalin with quizalofop-p-ethyl coupled with crop mulch resulted in season-long weed control and over 80% bulb yield (36.58 t/ha) gains compared to the weed-free condition. These findings emphasize the efficacy of combining herbicides and mulches as an integrated weed management strategy for onions. By adopting such integrated approaches, farmers could improve weed control while maintaining bulb yield and quality, reducing the risks associated with herbicide resistance, and promoting sustainable onion production in the north-western Indo-Gangetic Plains.